Glucocorticoid receptor variants in childhood attention-deficit/hyperactivity disorder and comorbid psychiatric disorders. (30th December 2016) - Schote, Andrea B.; Bonenberger, Martina; Pálmason, Haukur; Seitz, Christiane; Meyer, Jobst; Freitag, Christine M.
Abstract: Stress results in a variety of neuroendocrine, immune and behavioral responses and represents a risk factor for many disorders. Following exposure to stress, glucocorticoids are secreted from the adrenal cortex and act via the ligand-activated glucocorticoid receptor (GR). Several polymorphisms of the GR-encoding gene NR3C1 have been described and functionally investigated. However, the impact of these variants on complex diseases such as Attention-Deficit/Hyperactivity Disorder (ADHD) is still unclear. In this study, 251 children with ADHD, 19 affected and 35 unaffected siblings, and their parents were included in a family-based association study assessing seven common variants of NR3C1 ( TthIII I_rs10052957; NR3C1-I_rs10482605; ER22/23EK_rs6189/rs6190; N363S_rs56149945; Bcl I_rs41423247; GR-9beta_rs6198). A four-marker haplotype ( TthIII I-NR3C1-I-ER22/23EK) was nominally associated with ADHD. In addition, in index children with ADHD, associations with comorbid disorders, inattentive and hyperactive-impulsive symptoms were explored. N363S minor allele carriers were more likely to show comorbid conduct disorder (CD). In our study, NR3C1 variants moderately affected ADHD and had a significant effect on comorbid CD. Therefore, NR3C1 as an important gene of the hypothalamic–pituitary–adrenal axis seems to be particularly relevant for the pathophysiology of ADHD combined with comorbid CD. For a deeper understanding, investigations in larger samples of healthy, ADHD and CD individuals are warranted. Highlights: We studied the effect of functional polymorphisms of the GR-encoding gene ( NR3C1 ). A nominally significant effect was observed for a rare haplotype with ADHD. Minor N363S G-allele carriers were more likely to show conduct disorder (CD). GR variants seem to be especially relevant for the pathophysiology of ADHD+CD.